Kazakhstan tulips: comparative analysis of complete chloroplast genomes of four local and endangered species of the genus Tulipa L. - Tussipkan, Dilnur; Shevtsov, Vladislav; Ramazanova, Malika; Rakhimzhanova, Aizhan; Shevtsov, Alexandr; Manabayeva, Shuga (Frontiers in Plant Science, 2024)
The present study is the first report on typical features of the complete chloroplast genome sequence of four local and endangered species including T. alberti, T. kaufmanniana, T. greigii, and T. dubia from Kazakhstan. The comparative analyses revealed that the complete genomes of four species were highly conserved in terms of total genome size (152. 006 bp -152. 382 bp), including a pair of inverted repeat regions (26. 330 bp -26. 371 bp), separated by a large single copy region (82.169 bp -82,378 bp) and a small copy region (17.172 bp -17.260 bp). , gene number (131), and intron length (540 bp -2620 bp) of 28 genes. The complete genomes of four species showed high nucleotide diversity (Pi=0.54058). The total number of SSR loci was 159 in T. alberti, 158 in T. kaufmanniana, 174 in T. greigii, and 163 in T. dubia. The result indicated that ten CDS genes, namely rpoC2, cemA, rbcL, rpl36, psbH, rps3, rpl22, ndhF, ycf1, and matK, with effective polymorphic SSRs, high sequence variability (SV) ranging from 2.581 to 6.102, and high nucleotide diversity (Pi) of these loci ranging from 0,004 to 0,010. For all intergenic regions longer than 150 bp, twenty-one most variable regions were found with high sequence variability (SV) ranging from 4,848 to 11,862 and high nucleotide diversity (Pi) ranging from 0,01599 to 0,01839. RSCU analysis was used to identify overrepresented and underrepresented codons for each amino acid. Based on the phylogenic analysis, the sequences clustered into four major groups, reflecting distinct evolutionary lineages corresponding to the subgenera Eriostemons, Tulipa, and Orithyia. Notably, T. greigii was distinctively grouped with species from Orithyia and Eriostemons rather than with other Tulipa species, suggesting a unique evolutionary history potentially shaped by geographical isolation or specific ecological pressures. The complete chloroplast genome of the four Tulipa species provides fundamental information for future research studies, even for designing the high number of available molecular markers.